Cedrol attenuates acute ischemic injury through inhibition of microglia-associated neuroinflammation via ERβ-NF-κB signaling pathways - Yu Bi; Ziyi Xie; Xiang Cao; Huanyu Ni; Shengnan Xia; Xinyu Bao; Qinyue Huang; Yun Xu; Qingxiu Zhang (Brain Research Bulletin)
Microglia-associated neuroinflammation plays essential roles in pathology of acute stroke. Cedrol, a natural compound extracted from ginger, has been shown to confer inhibitory effects on inflammation in various diseases. However, whether Cedrol suppresses neuroinflammation and protects brains from acute ischemic injury still remains unclear. In this study, we found that Cedrol inhibited microglia activation and the production of inflammatory factors in LPS-challenged microglia and the penumbra region of middle cerebral artery occlusion (MCAO) mice. We also found that Cedrol reduced the infarct size and mNSS scores and improved acute cerebral ischemia-induced behavioral outcomes, suggesting remarked neuroprotection of Cedrol. Molecular docking analysis showed that Cedrol bound to estrogen receptor β (ERβ) with moderate-strong affinity. Intriguingly, treatment with fulvestrant, an ER blocker, abolished the anti-inflammatory effects of Cedrol. Cedrol significantly reversed the LPS- and MCAO-induced increases in phosphorylation levels of IκB and NF-κB P65 in primary microglia and MCAO mice, respectively. Additionally, Cedrol was observed to rescue LPS-induced shuttling of NF-κB P65 from cytoplasm to nuclei in primary microglia, indicating inhibitory effects of Cedrol on NF-κB signaling. These results suggest microglia associated neuroinflammation may be mediated by ERβ-NF-κB signaling pathway. Together, our study reveals that Cedrol protected brain function from acute cerebral ischemia through inhibition of microglia-associated neuroinflammation via ERβ-NF-κB signaling pathways, and Cedrol may serve as an alternative option for treatment of acute stroke injury.